ANALISIS IMPLEMENTASI METODE QIRO’AH DALAM PEMBELAJARAN BAHASA ARAB SISWA KELAS IX C DI MTs IRSYADUN NASYI’IN - Ramadhani, Muhammad Zidan; Kafi, Fina Aunul (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This study was motivated by the low ability of students to understand Arabic texts in Arabic language learning for class IX C at MTs Irsyadun Nasyi’in. Students still experienced difficulties in reading, comprehending texts, and mastering basic Arabic grammar such as nahwu and sharaf. This study aimed to describe the implementation of the Qiro’ah method in Arabic language learning and to identify the obstacles and teacher strategies in improving students’ reading skills. This study employed a qualitative approach with a case study design. The research subjects consisted of an Arabic language teacher and students of class IX C. Data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. Data validity was examined using source triangulation and technique triangulation. The findings revealed that the implementation of the Qiro’ah method was carried out through planning, implementation, and evaluation stages. The teacher applied vocabulary and grammatical approaches by emphasizing the mastery of nahwu and sharaf as the foundation for understanding Arabic texts. The implementation of the Qiro’ah method gradually improved students’ participation and reading ability. However, several obstacles were still found, including low learning motivation, limited vocabulary mastery, weak understanding of Arabic grammar, and limited learning media and Arabic-speaking environment. To overcome these obstacles, the teacher conducted reading habituation, provided learning motivation, and applied more varied learning strategies. Therefore, the Qiro’ah method can be considered an alternative learning method to improve students’ Arabic reading skills and text comprehension. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan peserta didik dalam memahami teks bahasa Arab pada pembelajaran bahasa Arab kelas IX C di MTs Irsyadun Nasyi’in. Peserta didik masih mengalami kesulitan dalam membaca, memahami isi bacaan, serta menguasai kaidah dasar bahasa Arab seperti nahwu dan sharaf. Penelitian ini bertujuan untuk mendeskripsikan penerapan metode Qiro’ah dalam pembelajaran bahasa Arab serta mengetahui hambatan dan strategi guru dalam meningkatkan kemampuan membaca peserta didik. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Subjek penelitian terdiri atas guru mata pelajaran bahasa Arab dan peserta didik kelas IX C. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diuji menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa penerapan metode Qiro’ah dilakukan melalui tahap perencanaan, pelaksanaan, dan evaluasi pembelajaran. Guru menerapkan pendekatan mufrodat dan gramatikal dengan menekankan penguasaan nahwu dan sharaf sebagai dasar memahami teks bahasa Arab. Penerapan metode Qiro’ah mampu meningkatkan keaktifan dan kemampuan membaca peserta didik secara bertahap. Namun, masih ditemukan beberapa hambatan, seperti rendahnya motivasi belajar, keterbatasan penguasaan kosakata, lemahnya pemahaman kaidah bahasa Arab, serta keterbatasan media dan lingkungan berbahasa Arab. Untuk mengatasi hambatan tersebut, guru melakukan pembiasaan membaca, memberikan motivasi belajar, dan menggunakan strategi pembelajaran yang lebih variatif. Dengan demikian, metode Qiro’ah dapat menjadi salah satu alternatif pembelajaran yang membantu meningkatkan kemampuan membaca dan pemahaman teks bahasa Arab peserta didik.